TIMING OF INOCULATION WITH SELECTED WINE BACTERIA ON THE KINETICS OF MALOLACTIC FERMENTATION AND SENSORY PROPERTIES OF VRANEC WINE FROM TIKVESH WINE REGION - Goran Milanov; Dushko Nedekovski; Milena Taseski-Gjorgjijevski (Faculty of Agricultural Sciences and Food, 2019)
The aim of this investigation is to determine the influence of timing of inoculation of four different lactic bacterias by co inoculation during the fermentation and post-fermentation of Vranec variety, to obtain more balanced wines with refined aromas. VP 41, ML Prime, O-Mega and PN4 are the types of commercial available lactic bacterias produced by Lallemand producer, used in malolactic fermentation (MLF) of wine Vranec. The kinetic of transformation of malic into lactic acid was measured. Also, chemical composition of wine (alcohol strength, specific gravity, total extract, total acids, volatile acids, pH, free and total SO2) wasperformed. The sensory descriptive analysis was performed. Seven wine experts were involved for the descriptive evaluation of the investigated wines.
Keywords: Vranec, lactic bacteria, MLF, sensory evaluation